PENERAPAN MANAJEMEN RISIKO DALAM MEMINIMALISIR KREDIT BERMASALAH KREDIT GUNA BHAKTI BANK BJB - Meara Benita Wipudiari (2021)
In carrying out its activities, banks must be able to maintain public trust and provide the best service. The Guna Bhakti Credit Product is a superior loan product of Bank BJB which in carrying out its activities cannot be separated from credit risk. Therefore, it is necessary to implement a good Risk Management process to avoid the occurrence of risks that can result in unwanted losses. This writing aims to determine the factors causing the risk of Guna Bhakti Credit, the application of Risk Management to manage and control risk, and the actions taken to deal with the risks that occur. The results of this paper indicate that the factors that cause risk are customers, banks, and external factors. The process of implementing risk management is carried out through risk identification, risk measurement, risk monitoring, and risk control. Risk mitigation is carried out by analyzing credit based on the 5C principles (Character, Capacity, Capital, Collateral, and Condition) and Installment Reserves and handling them by providing warning letters and through insurance.